Highly Transparent, Self-Healing, and Self-Adhesive Double Network Hydrogel for Wearable Sensors - Chen, Kai; Liu, Mingxiang; Wang, Feng; Hu, Yunping; Liu, Pei; Li, Cong; Du, Qianqian; Yu, Yongsheng; Xiao, Xiufeng; Feng, Qian (Frontiers in Bioengineering and Biotechnology, 2022)
Hydrogel-based flexible electronic devices are essential in future healthcare and biomedical applications, such as human motion monitoring, advanced diagnostics, physiotherapy, etc. As a satisfactory flexible electronic material, the hydrogel should be conductive, ductile, self-healing, and adhesive. Herein, we demonstrated a unique design of mechanically resilient and conductive hydrogel with double network structure. The Ca2+ crosslinked alginate as the first dense network and the ionic pair crosslinked polyzwitterion as the second loose network. With the synthetic effect of these two networks, this hydrogel showed excellent mechanical properties, such as superior stretchability (1375%) and high toughness (0.57 MJ/m3). At the same time, the abundant ionic groups of the polyzwitterion network endowed our hydrogel with excellent conductivity (0.25 S/m). Moreover, due to the dynamic property of these two networks, our hydrogel also performed good self-healing performance. Besides, our experimental results indicated that this hydrogel also had high optical transmittance (92.2%) and adhesive characteristics. Based on these outstanding properties, we further explored the utilization of this hydrogel as a flexible wearable strain sensor. The data strongly proved its enduring accuracy and sensitivity to detect human motions, including large joint flexion (such as finger, elbow, and knee), foot planter pressure measurement, and local muscle movement (such as eyebrow and mouth). Therefore, we believed that this hydrogel had great potential applications in wearable health monitoring, intelligent robot, human-machine interface, and other related fields.